Taxes on Sugar-Sweetened Beverages : International Evidence and Experiences - Hattersley, Libby; Thiebaud, Alessia; Fuchs, Alan; Gonima, Alberto; Silver, Lynn; Mandeville, Kate (World Bank, Washington, DC, 2021)
Taxes on SSB are an increasingly popular fiscal policy for health. This brief summarizes the latest evidence on SSB tax implementation and effectiveness to support governments who are considering, or are in the process of developing, an SSB tax. Further details and references can be found in the accompanying report (World Bank 2020).